A Banks Customer Citizenship Behaviour in the Multinomial Logistic Regression Model - Adirek Vajrapatkul; Nuttawut Rojniruttikul (My University, 2024)
This research aimed to study the factors affecting customer citizenship behavior (CCB) in the banking industry. The data were collected from questionnaires from bank customers in six districts of Bangkok, Thailand. The data were analyzed using EFA and MLR techniques. The study identified three latent variables that could affect the level of CCB, namely good corporate governance, quality of self-service technology, and quality of on-site service. The results showed that good corporate governance in transparency, accountability, and fairness significantly improves the level of CCB. In addition, the quality of self-service technology, which provided convenience to bank customers, could lead to increased CCB. Regarding on-site service quality, the results also showed that it was an important factor in increasing CCB. In terms of the impact of demographic variables, people aged 41 to 45, women, and low-income earners were more likely to have high levels of CCB compared to the reference group. This research emphasizes the need to adhere to corporate governance, quality of self-service technology, quality of on-site service, and customer characteristics to enhance CCB and bank success.
Keywords: Customer Service Quality and Loyalty